Samuel Richardson : a Man of Letters. - Flynn, Carol Houlihan (Princeton University Press, 2014)
Adding a lively voice to Richardsonian studies, Carol Houlihan Flynn traces the complex workings of a major literary imagination. Originally published in 1982. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly herita.
Keywords: Richardson, Samuel, -- 1689-1761 -- Criticism and interpretation.; Richardson, Samuel, -- 1689-1761; Epistolary fiction, English -- History and criticism.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; LITERARY CRITICISM -- European -- General.; Epistolary fiction, English; Criticism, interpretation, etc.